Comparison of scanning electron microscopy findings regarding biofilm colonization with microbiological results in nasolacrimal stents for external, endoscopic and transcanalicular dacryocystorhinostomy - ÇETİNEL, ŞULE (IJO PRESS, 2014)
AIM: To compare bacterial biofilm colonization in lacrimal stents following external dacryocystorhinostomy (EX DCR), endoscopic dacryocystorhinostomy (EN-DCR), and transcanalicular dacryocystorhinostomy (TC-DCR) with multidiode laser. METHODS: This prospective study included 30 consecutive patients with nasolacrimal duct obstruction who underwent EXT-, EN-, or TC-DCR. Thirty removed lacrimal stent fragments and conjunctival samples were cultured. The lacrimal stent biofilms were examined by scanning electron microscopy (SEM). RESULTS: ElevEN-(36.7%) of the 30 lacrimal stent cultures were positive for aerobic bacteria (most commonly Staphylococcus spia'arrniokS and Pseudomonas aeruginosa). However anaerobic bacteria and fungi were not identified in the lacrimal stent cultures. Twenty sevEN-(90%) patients had biofilm positive lacrimal stents. The conjunctival culture positivity after the DCR, biofilm positivity on stents, the grade of biofilm colonization, and the presence of mucus and coccoid and rod shaped organisms did not significantly differ betweEN-any of the groups (P>0.05). However, a significant difference was found whEN-the SEM results were compared to the results of the lacrimal stent and conjunctival cultures (P<0.001). CONCLUSION: Type of dacryocystorhinostomy (DCR) surgery did not affect the biofilm colonization of the lacrimal stents. SEM also appears to be more precise than microbiological culture for evaluating the presence of biofilms on lacrimal stents.
Keywords: biofilms; nasolacrimal duct obstruction; epiphora; dacryocystitis; scanning electron microscopy; CLINICALLY NONINFECTED EYES; BACTERIAL BIOFILMS; MICROBIAL-GROWTH; RUTHENIUM RED; IN-VITRO; ENDOPHTHALMITIS; INFECTIONS; KERATITIS; SURFACES; EPIPHORA